Concept of Constrained Translation. Non-Linguistic Perspectives of Translation - Mayoral, Roberto; Kelly, Dorothy; Gallardo, Natividad (Meta, 1988)
AbstractThe procedures involved in the translation of texts have been widely studied from a linguistic point of view. However, when translation is required not only of written texts alone, but of texts in association with other communication media (image, music, oral sources, etc.), the translator's task is complicated and at the same time constrained by the latter. We introduce in this paper the concept of constrained translation from the point of view of communication theory (as defined by the terminology of Nida "dynamic translation") ; we also deal with the existence of more than one communication channel, the factors of source culture, target culture, "noise", and the role of the translator in this complex process.